Effect of different simulated altitudes on repeat-sprint performance in team-sport athletes - Goods, P. S. R.; Dawson, B. T.; Landers, G. J.; Gore, C. J.; Peeling, P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This study aimed to assess the impact of 3 heights of simulated altitude exposure on repeat-sprint performance in teamsport athletes. Methods: Ten trained male team-sport athletes completed 3 sets of repeated sprints (9 × 4 s) on a nonmotorized treadmill at sea level and at simulated altitudes of 2000, 3000, and 4000 m. Participants completed 4 trials in a random order over 4 wk, with mean power output (MPO), peak power output (PPO), blood lactate concentration (Bla), and oxygen saturation (SaO2) recorded after each set. Results: Each increase in simulated altitude corresponded with a significant decrease in SaO2. Total work across all sets was highest at sea level and correspondingly lower at each successive altitude (P < .05; sea level < 2000 m < 3000 m < 4000 m). In the first set, MPO was reduced only at 4000 m, but for subsequent sets, decreases in MPO were observed at all altitudes (P < .05; 2000 m < 3000 m < 4000 m). PPO was maintained in all sets except for set 3 at 4000 m (P < .05; vs sea level and 2000 m). BLa levels were highest at 4000 m and significantly greater (P < .05) than at sea level after all sets. Conclusions: These results suggest that "higher may not be better," as a simulated altitude of 4000 m may potentially blunt absolute training quality. Therefore, it is recommended that a moderate simulated altitude (2000-3000 m) be employed when implementing intermittent hypoxic repeat-sprint training for team-sport athletes.